Local surgical therapy of melanoma - Witkowski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2003)
The primary local surgical excision of malignant melanoma has been analyzed on the basis of current literature. Logical and scientific basis of preferred melanoma primary excision margins related to the author’s clinical experience as well as medical literature facts is fully discussed. Operational and reconstructive technique principles of post-excisional defect closing are stated. Treatment of a primary melanoma involves local excision (or reexcision) of the tumour with a margin of skin and subcutaneous tissue to reduce the risk of local recurrence. The excision margin chosen depends on the histopathological features of the melanoma, in general the tumour thickness is the most important consideration. In recent years the wide excision margin of primary melanoma have been reduced in practice accordingly to a few randomized as well as clinical prospective studies of national Melanoma Groups sharing the opinions that excision margins reduction does not have a disadvantageous influence on local melanoma recurrence rate. This point of view is not proven properly yet by adequate randomized trials only in melanomas considered to be thick >4 mm. The conformity of MGs recommendation of excision margin exists in cases of stage I melanoma in situ (pTIS) – the 2–5 mm margin is advised. The melanoma 4 mm thick (pT4) should be surgically removed with a margin of 2–3 cm, preferred by majority of MGs is 2 cm. There is no evidence of excising the deep fascia to be more beneficial for prognosis of malignant melanoma. When primary closure of postexcisional defect is impossible, the flap or skin graft technique of defect closing is advised to be applied, on the basis of clinical considerations.